Efektivitas Melipat Kertas Dalam meningkatkan Kemampuan Motorik Halus Pada Anak Usia 5-6 Tahun di TK Islam Sukoharjo 2 Lampung - Hasanah Hasanah; Elva Wardani Harahap; Hesi Kartikasari Harahap (Jurnal Pendidikan Tuntas, 2023)
Fine motor skills in children are different, there are delays and of course normal ones are skills that use the fingers, hands and wrist movements appropriately. In order not to experience developmental delays, attention needs to be given to this matter from an early age in the child's development. This research seeks to examine the effectiveness of paper folding in improving fine motor skills in children aged 5-6 years at the Islamic Kindergarten Sukoharjo 2 Lampung, by carrying out two cycles and each cycle being held three meetings, with research subjects being Group B aged 5-6 years. totaling 15 people, and data collection in this study used observation and documentation techniques. Paper folding activities to improve the fine motor skills of children aged 5-6 years at TK Islamiyah Sukoharjo 2, Lampung, gave positive results. This increase is clearly illustrated in the graph which shows the increase in children's developmental achievements, especially children's fine motor skills from Pre-Cycle, Cycle I, to Cycle II. The results are that at the pre-cycle stage, 67% of children were in the Undeveloped category, but after Cycle I, this figure fell to 33%. Likewise, the Beginning to Develop category experienced an increase, from 27% in the pre-cycle to 33% after Cycle I. This increase reflects the positive impact of research actions on the children's fine motor skills. An increase also occurred in the Developing According to Expectations category, which initially only reached 7%, after Cycle I it increased to 27%. Furthermore, the Very Well Developing category also experienced an increase, where previously it was only 0%, after Cycle I it increased to 7%. Even though there has been an increase, this achievement figure still has not reached the expected standard of success. So that cycle II was carried out, the results in percentage terms showed a significant increase. The highest percentage was 73% of children in the Developing According to Expectations category, followed by 20% of children in the Very Well Developing category, and 7% of children still in the Starting to Develop category. The increase seen in the diagram above shows that the average fine motor skills of children aged 5-6 years have increased, which can be considered an indicator of success in this classroom action research. Keywords: Activities, Paper Folding, Children's Fine Motor